Prolonging the circulatory retention of SPIONs using dextran sulfate: in vivo tracking achieved by functionalisation with near-infrared dyes. (9th October 2014) - Abdollah, Maha R. A.; Kalber, Tammy; Tolner, Berend; Southern, Paul; Bear, Joseph C.; Robson, Mathew; Pedley, R. Barbara; Parkin, Ivan P.; Pankhurst, Quentin A.; Mulholland, Paul; Chester, Kerry
Abstract : The rapid reticuloendothelial system (RES) mediated clearance of superparamagnetic iron oxide nanoparticles (SPIONs) from circulation is considered a major limitation of their clinical utility. We aimed to address this by using dextran sulfate 500 (DSO4 500), a Kupffer cell blocking agent, to prolong SPIONs circulatory time. Blood concentrations of SPIONs are difficult to quantify due to the presence of haemoglobin. We therefore developed methods to functionalise SPIONs with near-infrared (NIR) dyes in order to trace their biodistribution. Two SPIONs were investigated: Nanomag®-D-spio-NH2 and Ferucarbotran. Nanomag®-D-spio-NH2 was functionalised using NHS ( N -hydroxysuccinimide) ester NIR dye and Ferucarbotran was labelled using periodate oxidation followed by reductive amination or a combination of EDC (ethyl(dimethylaminopropyl) carbodiimide )/NHS and click chemistries. Stability after conjugation was confirmed by dynamic light scattering (DLS), superconducting quantum interference device (SQUID) and transmission electron microscopy (TEM). In vivo experiments with the functionalised SPIONs showed a significant improvement in SPIONs blood concentrations in mice pre-treated with dextran sulfate sodium salt 500 (DSO4 500).